Video-Oculography During Free Visual Exploration to Detect Right Spatial Neglect in Left-Hemispheric Stroke Patients With Aphasia: A Feasibility Study - Kaufmann, Brigitte C.; Cazzoli, Dario; Koenig-Bruhin, Monica; Müri, René M.; Nef, Tobias; Nyffeler, Thomas (Frontiers in Neuroscience, 2021)
Spatial neglect has been shown to occur in 17-65% of patients after acute left-hemispheric stroke. One reason for this varying incidence values might be that left-hemispheric stroke is often accompa-nied by aphasia, which raises difficulties in assessing attention deficits with conventional neuropsy-chological tests entailing verbal instructions. Video-oculography during free visual exploration (FVE) requires only little understanding of simple non-verbal instruction and has been shown to be a sensitive and reliable tool to detect spatial neglect in patients with right-hemispheric stroke. In the present study, we aimed to investigate the feasibility of FVE to detect neglect in 10 left-hemispheric stroke patients with mild to severe aphasia as assessed by means of the Token Test, Boston Naming Test and Aachener Aphasie Test. The patient's individual deviation between eye movement calibration and validation was recorded and compared to 20 age-matched healthy controls. Furthermore, typical FVE parameters such as the landing point of the first fixation, the mean gaze position (in ° of visual angle), the number and duration of visual fixations and the mean visual exploration area were compared between groups. In addition, to evaluate for neglect, the Bells cancellation test was performed and neglect severity in daily living was measured by means of the Catherine Bergego Scale (CBS). Our results showed that the deviation between calibration and validation did not differ between aphasia patients and healthy controls highlithing its feasibility. Furthermore, FVE revealed the typical neglect pattern with a significant leftward shift in visual exploration bahaviour, which highly correlated with neglect severity as assessed with CBS. The present study provides evidence that FVE has the potential to be used as a neglect screening tool in left-hemispheric stroke patients with aphasia in which compliance with verbal test instructions may be compromised by language deficits.